Proton Strategic Positioning as Cost Leadership in the Malaysian Market - Laith Ali Zgair Gharan (Peerian Journals Publishing, 2025)
The automotive industry in Malaysia was traditional dominated by the Proton, the national carmaker. Recently, there are some other players in the market and some regional and international players have entered the market as well. The car that provides the customers with good quality and low prices. The company position itself as cost leadership. The paper aim to review the strategic positioning of the company as cost leadership. The literature was reviewed on the topic related to cost leadership and other generic strategic of Porter. A profile of the company is presented with its mission and vision. According to a review of all the literature and the company profile. It was found that the company does not have the cost leadership characteristics. Other local companies provide better products and low prices than Proton. In addition, regional carmakers such as KIA are also providing good quality with comparatively low or similar prices.
Keywords: companies; leadership; strategic